Timing's Influence on the Efficacy of Heritage Impact Assessment: A Qualitative Comparative Analysis: The role of Heritage impact assessment in managing World Heritage Site - Fanit, Souaad; Chabi, Nadia (Future Science, 2023)
This study aims to emphasize the growing importance of Heritage Impact Assessment in managing world cultural heritage, as it faces various challenges posed by urban development policies. Heritage Impact Assessment is seen as a crucial tool for achieving the balance between preserving cultural heritage and fostering development. The study focuses on the outcomes of the application of Heritage Impact Assessment in five world cultural heritage sites, each facing unique development projects, located in different countries. A case study research method was adopted to provide an in-depth analysis within specific contexts. The results were obtained through a comparative qualitative analysis, which aimed to gain a deeper understanding of the correlation between the timing of implementation and its connection to the efficacy of the evaluation. The results showed that the timing of the implementation of Heritage Impact Assessment can have a significant impact on the final outcome of the evaluation but other factors also play a role, adequate methodology, contextual, and institutional factors. The results demonstrated the two-fold nature of heritage impact assessment, dependent on the time of application: proactive assessment, which helps enhance the world heritage's resilience and prepare it for future development initiatives, and curative assessment, which serves as a corrective measure for specific projects.